Berpikir kritis dengan logika: Memahami Silogisme, Logisme, dan Fallacy - Kadrina, Lilatul (Maliki Interdisciplinary Journal, 2025)
The development of communication technology, social media, limited natural resources, and dynamic social change demand strong critical thinking skills. Critical thinking is a mental process for evaluating the truth of a statement, making decisions, and applying reasoning effectively, in contrast to logical thinking, which focuses on drawing conclusions. Logical thinking skills include understanding basic concepts, syllogisms, and recognizing fallacies, which are essential for constructing sound arguments and avoiding flawed reasoning. Syllogisms, as a form of deductive reasoning, help connect major and minor premises to produce logical conclusions, while fallacies arise from inaccuracies in language or relevance, whether intentional or not, and are often used to influence opinion. This article discusses the relationship between critical and logical thinking, the application of syllogisms, and the identification of fallacies, as an effort to improve analytical skills, argument evaluation, and rational decision-making in today's information age.